Digital illustration as visual communication to promote Kelantan cultural heritage / Roziani Mat Nashir@Mohd Nasir and Ghazali Daimin - Mat Nashir@Mohd Nasir, Roziani; Daimin, Ghazali (Universiti Teknologi MARA, Perak, 2022)
The state of Kelantan Darul Naim is endowed with a wealth of tourist attractions, including the oldest tropical rainforest, exclusive and distinctive art experiences and activities, mouthwatering local traditional food, and welcoming local people. Kelantan is regarded as the "cradle of Malay culture". There is a lot of cultural performance that can be found in Kelantan such as Wayang Kulit (shadow puppet), Menora, Mak Yong and Dikir Barat. Apart from that, Kelantan is also well-known for traditional games and musical instruments such as gasing, Wau Bulan, keretuk, and rebana ubi. The methods used in this research is a questionnaire and content analysis used to analyze the vector and raster digital illustration artwork from a selected university in Kelantan which offers creative digital illustration subject as a requirement. Results found that the students can produce both vector and raster by using Kelantan cultural heritage as the subject matter. In a conclusion, digital illustration can be used as visual communication to promote Kelantan cultural heritage in the future.